Cognitive Control of Episodic Memory in Schizophrenia: Differential Role of Dorsolateral and Ventrolateral Prefrontal Cortex - Ragland, John D.; Ranganath, Charan; Phillips, Joshua; Boudewyn, Megan A.; Kring, Ann M.; Lesh, Tyler A.; Long, Debra L.; Luck, Steven J.; Niendam, Tara A.; Solomon, Marjorie; Swaab, Tamara Y.; Carter, Cameron S. (Frontiers in Human Neuroscience, 2015)
Background. Dorsal (DLPFC) and ventral (VLPFC) subregions in lateral prefrontal cortex play distinct roles in episodic memory, and both are implicated in schizophrenia. We test the hypothesis that schizophrenia differentially impairs DLPFC versus VLPFC control of episodic encoding. Methods. Cognitive control was manipulated by requiring participants to encode targets and avoid encoding nontargets based upon stimulus properties of test stimuli (i.e., the match or miss-match of the color of the word and a surrounding frame). The more automatic encoding response (target versus nontarget) was predicted to engage VLPFC in both groups. Conversely, having to overcome the prepotent encoding response (nontargets versus targets) was predicted to produce greater DLPFC activation in controls than in patients. Encoding occurred during event-related fMRI in a sample of 21 individuals with schizophrenia and 30 healthy participants. Scanning was followed by recognition testing outside the scanner. Results. Patients were less successful differentially remembering target versus non-target stimuli, and retrieval difficulties correlated with more severe disorganized symptoms. As predicted, the target versus nontarget contrast activated the VLPFC and correlated with retrieval success in both groups. Conversely, the nontarget versus target contrast produced greater DLPFC activation in controls than in patients, and DLPFC activation correlated with performance only in controls. Conclusions. Individuals with schizophrenia can successfully engage the VLPFC to provide control over semantic encoding of individual items, but are specifically impaired at engaging the DLPFC to provide control over rule-guided encoding decisions. This extends previous cognitive control models based on response selection tasks to the memory domain.